Inventory of the sites of geological interest, in the southwestern of Antioquia Colombia. (2017)
This research sought, the inventory of sites of geological interest, in the southwestern Antioquia region consists of 24 municipalities and a total area of 6513 km2, taking as a scale for analysis 1: 25,000 and used several sources of primary information and secondary. The methodology used was exploratory and was based on: literature review, collection of primary data through virtual and surveys, fieldwork for the surveys, visiting outstanding sites and a workshop in schools, finally ending with integration and analysis of all information collected. As important results, it has an inventory of 168 points of geological interest, which is noted for its natural intrinsic attributes or tourism management plans and associated conservation. Of these, 44 sites stand out for their recognition among population, listed among the first, Cerro Tusa (20.1%) of La Pintada Farallones (12.4%), the Citara Farallones (7.7%), the Paramo del Sol and Cerro Bravo (7.1). Finally, municipalities with a larger number of geological sites of interest were reported Jardín (11.9%), Caicedo (11.3%) and Andes, Jericó y La Pintada (6%), and fewer reports Betania who obtained (0.6%).